2010
DOI: 10.1021/jz1007998
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of A New Al Species in Hydrogen Reactions of NaAlH4

Abstract: The NaAlH4 system remains the archetype of hydrogen storage solids. However, the detailed mechanisms of the hydrogen reactions of NaAlH4 remain unknown. We report 27Al in situ nuclear magnetic resonance (NMR) spectroscopic data revealing an Al-bearing mobile species that could provide the large scale metal-atom transport needed for rehydriding. This new species forms under reaction conditions but can be captured at ambient temperature using excess H2 pressure. The NMR measurements demonstrate that the species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
67
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(75 citation statements)
references
References 38 publications
6
67
2
Order By: Relevance
“…3 we report their fits showing how the s (Q,E) (see also Appendix A) spectra from samples 2 and 4 can be quite satisfactorily reconstructed by a simple linear combination of their thermally untreated components: Na 3 AlH 6 plus NaAlH 4 or NaH [24] ( 2 = 0.61 and 0.62, respectively), leaving no unaccounted vibrational features. Thus, under the conditions of our experiments, after our thermal treatment we have found no evidence for the recently discovered by 27 Al NMR [25] highly defective AlH 5 2-species. However, these may exist only locally, as an out-ofequilibrium short-lived species near defects created by Ti atoms, for instance.…”
Section: Discussioncontrasting
confidence: 84%
“…3 we report their fits showing how the s (Q,E) (see also Appendix A) spectra from samples 2 and 4 can be quite satisfactorily reconstructed by a simple linear combination of their thermally untreated components: Na 3 AlH 6 plus NaAlH 4 or NaH [24] ( 2 = 0.61 and 0.62, respectively), leaving no unaccounted vibrational features. Thus, under the conditions of our experiments, after our thermal treatment we have found no evidence for the recently discovered by 27 Al NMR [25] highly defective AlH 5 2-species. However, these may exist only locally, as an out-ofequilibrium short-lived species near defects created by Ti atoms, for instance.…”
Section: Discussioncontrasting
confidence: 84%
“…28 Similar effects might occur in LiBH 4 . The mobile BH 4 − species could possibly be formed in the bulk material too without the presence of a nanoporous material.…”
Section: ■ Experimental Sectionmentioning
confidence: 72%
“…At this point, Reaction 2 is thermodynamically favorable, and there is a coexistence of molten NaAlH 4 with solid Na 3 AlH 6 , Al, and NaH. In addition, Gross 27,33 and the existence of a new γ-NaAlH 4 phase has been proposed based on theoretical calculations. 34 In contrast, Gross et al 32 clearly showed that Ti-doped systems decompose according to Reaction 1 when the temperature is only 100°C.…”
Section: ' Introductionmentioning
confidence: 99%